Kelompok Usaha Kecil Pembibitan Tanaman Bunga di Banyuurip Gresik - Dyah Rini Prihastuty; Sri Rahayuningsih (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The purpose of this Partnership Program for People is to provide Appropriate Technology for Small Businesses engaged in flower plant nursery. The target of this partnership program for the community is business owners in the field of flower plant nursery. The problem faced by flower plant nursery SMEs is the absence of appropriate equipment or technology in supporting flower plant nursery activities, besides that business management practices have not been touched in doing business, for example simple financial painting and promotion through social media. The proposer of the partnership program in the community agreed with partners to procure appropriate technology in the form of water reservoirs in the implementation of flower plant nurseries, in addition to providing training and assistance in business management and promotion. The operation of the water reservoir will facilitate watering of flower plant seedlings, so that productivity increases. The provision of business management training and assistance has also increased its sales turnover, so that the welfare of flower plant nursery SMEs can be better.